1996
DOI: 10.1523/jneurosci.16-20-06504.1996
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of Spatial Mental Imagery Generated from Verbal Instructions

Abstract: Positron emission tomography (PET) was used to monitor regional cerebral blood flow variations while subjects were constructing mental images of objects made of three-dimensional cube assemblies from auditorily presented instructions. This spatial mental imagery task was contrasted with both passive listening (LIST) of phonetically matched nonspatial word lists and a silent rest (REST) condition. All three tasks were performed in total darkness. Mental construction (CONS) specifically activated a bilateral occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
153
2
13

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(196 citation statements)
references
References 38 publications
(55 reference statements)
28
153
2
13
Order By: Relevance
“…Similar patterns of activation have been observed in studies of the manipulation of visuo-spatial information [19] and allocentric relations [20].…”
Section: The Neural Substrates Of Reasoning About Relationssupporting
confidence: 79%
“…Similar patterns of activation have been observed in studies of the manipulation of visuo-spatial information [19] and allocentric relations [20].…”
Section: The Neural Substrates Of Reasoning About Relationssupporting
confidence: 79%
“…For example, a study conducted by Just and colleagues [26] compared the cortical activation when participants either read or listened to high-and low-imagery sentences. The highimagery condition elicited greater activation in parietal and prefrontal regions similar to those observed in previous mental imagery studies [1,5,6,22,27,28]. In sum, language stimuli, in particular sentence stimuli, has been shown to elicit mental images in much the same way as non-verbal stimuli.…”
Section: Introductionsupporting
confidence: 84%
“…Previous studies have indicated that mental imagery generated from verbal instructions and from visual encoding activate similar cortical regions [22][23][24][25]. For example, a study conducted by Just and colleagues [26] compared the cortical activation when participants either read or listened to high-and low-imagery sentences.…”
Section: Introductionmentioning
confidence: 99%
“…1998), including mental imagery (Mellet et al. 1996; Kosslyn and Thompson 2003; Ganis et al. 2004; Mazard et al.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies was a report on pure obsessive–compulsive patients presenting the reduction of white matter adjacent to the right SMG as the sole finding (Mellet et al. 1996; Ganis et al. 2004; Slotnick et al.…”
Section: Discussionmentioning
confidence: 99%